The Influence Of Financial Ratio On Stock Prices In Manufacturing Companies Listed On The Indonesia Stock Exchange - Dahlia Gultom (JURNAL ILMIAH SOCIO SECRETUM, 2023)
The object studied in this study is a manufacturing company in the cosmetic and household sub-sectors listed on the Indonesia Stock Exchange for the period 2018-2020. The purpose of this study was to determine the effect of ROA, ROE, EPS on stock prices either partially or simultaneously. The sample in the study were 7 companies. The sampling technique is purposive sampling. The regression equation obtained in this study is Y = 6.036 – 2.397X_1 + 2.375X_2 – 0.074X_3. The results show that ROA partially has no effect on stock prices where the significant value is 0.220 > 0.05, ROE partially has no effect on stock prices where the significant value is 0.169 > 0.05, and EPS partially has no effect on stock prices where the significant value is 0.395. > 0.05. Simultaneously, the ROA, ROE, EPS variables have no significant effect on the stock price 0.165 > 0.05, and the Adjusted R Square value is 0.089. This means that 8.9% of the dependent variable or stock price is influenced by the independent variable, while the remaining 91.1 % is influenced by other variables not examined in this study.